2010
DOI: 10.2320/matertrans.m2010252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Additive during Thermal Reduction of Platinum Electrodes for Dye-Sensitized Solar Cells

Abstract: We report on a method to prepare Pt electrodes with homogeneously dispersed Pt nanoparticles on fluorine-doped tin oxide substrates by adding an organic additive, hydroxypropyl cellulose (HPC), in the Pt precursor solution for thermal decomposition on the substrates. The Pt electrodes prepared with various amounts of added HPC are characterized electrochemically by cyclovoltammetry and electrochemical impedance spectroscopy. The addition of HPC increases the surface area of the Pt electrode and, hence, the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The solution was spin-coated on the FTO glass and subjected to a thermal decomposition at 450 °C for 1 h, yielding a 20 nm thick Pt layer. [37] The size of the active area was ca. 1.66 ± 0.02 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The solution was spin-coated on the FTO glass and subjected to a thermal decomposition at 450 °C for 1 h, yielding a 20 nm thick Pt layer. [37] The size of the active area was ca. 1.66 ± 0.02 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, selection of the electrode is also important in the operation of solar cell. Several studies suggested that platinum can be a good electrode due to its excellent catalytic activity which can reduce the voltage loss during solar cell operation, and thus minimizing the energy loss [18,19]. In the present paper, fabrication of hybrid SM-PAni/ZnS nanocomposites grown on glass and Ptcoated substrates is reported.…”
Section: Introductionmentioning
confidence: 92%